Electrical stimulation and muscle strengthening - Dehail, P.; Duclos, C.; Barat, M. (Annales de Réadaptation et de Médecine Physique, 2008)
To identify the effects of application methods and indications of direct muscle electrostimulation on strength gain. Methods: Literature review and analysis of articles from Medline database with the following entries: muscular or neuromuscular, electromyostimulation, electrical stimulation, strengthening, strength training, immobilization, muscle dystrophy, bed-rest, bed-bound, knee or hip surgery, postoperative phase, cachexia, sarcopenia, and their French equivalent. Results: Because of its specific muscle recruitment order, different from that of voluntary contraction, direct muscle electrostimulation is theoretically a complementary tool for muscle strengthening. It can be used in healthy subjects and in several affections associated with muscle function loss. Its interest seems well-established for post-traumatic or postsurgery lower-limb immobilizations but too few controlled studies have clearly shown the overall benefits of its application in other indications. Whatever the indication, superimposed or combined electrostimulation techniques are generally more efficient than electrostimulation alone. Conclusion: Even though widely used, the level of evidence for the efficiency of electromyostimulation is still low. For strength gains, it yielded no higher benefits than traditional strengthening methods. Its interest should be tested in medical affections leading to major muscle deconditioning or in sarcopenia.